A 5G RURAL, REMOTE, AND DIFFICULT AREAS HOPE: A REVIEW - Harry Candra Sihombing (TEKNOKOM, 2021)
The 5G cellular networks are “urban” areas technology in nature, extensively deployed where the user’s density is high to provide very high data rates, coupled with extremely low delays and dealing with very high mobility of users. On the contrary, one-third of people experience a lack of mobile broadband connectivity living in rural zones. These mobile broadband lacks recognized as the main barriers impairing the Sustainable Developing Goals (SDGs) defined by the United Nations. Those that are not currently covered will be unlikely to be covered also soon, as the network operators are not keen to invest in such zones, because of potentially low revenues. While it is confirmed that 5G would meet stringent requirements in urban zones, rural areas still suffer from almost inexistent MBB (Mobile Broadband) coverage, especially in the developing world. The big deal of isolated rural areas, which are sparsely inhabited by low-income populations, is that the classical access using traditional backhaul technologies is a bad solution for operators since it does not ensure a good ROI (Return of Investment).